Tire-Pavement Contact Stress Characteristics and Critical Slip Ratio at Multiple Working Conditions - Minrui Guo; Xinglin Zhou (Advances in Materials Science and Engineering)
The contact stress distribution of tire-pavement is generally assumed to be uniformly distributed in circles or rectangles in the pavement design. This simplification can solve some common engineering problems, but it neglects two factors including magnitude and direction of the contact stress. The main purpose of this paper is to analyze the contact stress distribution between the bus tire and the pavement under different driving conditions and pinpoint and compare the critical slip ratio during braking and acceleration. First, a tire-pavement simulated contact model is constructed by ABAQUS. Next, we compare, respectively, contact stresses in the vertical, longitudinal, and transverse directions at various rolling conditions and analyze the longitudinal forces at different slip ratios during braking and acceleration. It is observed that the magnitude, direction, and nonuniform distribution of contact stress are affected by the multiple working conditions while the bus is working. Meanwhile, in the braking and acceleration conditions, the longitudinal force grows rapidly as the slip ratio increases, and then grows slowly and at last decreases when the critical slip ratio is reached. However, the critical slip ratio at the time of braking differs from that at the time of acceleration, and the former is smaller than the latter.